SINERGI HUBUNGAN INDUSTRIAL DAN IMPLEMENTASI UNDANG-UNDANG KETENAGAKERJAAN DALAM MEMINIMALKAN KONFLIK INDUSTRIAL - Aliffiah Novi Ramadhini; Herliana Diah Ayuningsih; Nurul Janah; Sesya Surya Safira; Zahra Khairunnisa; Arfian (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
Harmonious industrial relations play an important role in maintaining company stability and employee welfare. However, labor disputes often lead to worker protests due to ineffective communication and the inadequate implementation of labor regulations. This study aims to analyze the role of industrial relations and the implementation of Labor Law in preventing labor protests within companies. The research employs a literature review method with a descriptive qualitative approach by examining relevant journals, books, and legal regulations. The findings indicate that effective communication, the optimization of Bipartite Cooperation Institutions (LKS Bipartit), and compliance with labor regulations contribute significantly to reducing industrial conflicts. Therefore, the synergy between harmonious industrial relations and proper implementation of labor regulations can serve as an effective preventive strategy to minimize labor protests and support organizational sustainability.